A microstrip patch antenna design - Chow, Wai Tin (Nanyang Technological University, 2022)
This Final Year Project Report covers the Final Year’s student design of a microstrip patch antenna. The microstrip patch antenna will be designed with a rectangular patch using the aperture coupled feeding technique for a single-ended operation before extending it to differential-ended operation for radio frequency energy harvesting applications Literature research has been conducted on the basic theory for designing a microstrip patch antenna and on radio frequency energy harvesting systems. This is to understand how the microstrip patch antenna operates in a radio frequency energy harvesting system and to get the initial design procedures, configurations, and the design parameters of the microstrip patch antenna that has a rectangular-shaped patch and uses the aperture coupled feeding technique in both single-ended and differential ended operation. The initial design parameters and configurations obtained has been simulated and finetuned using a computer-aided design (CAD) tool, Ansys Electronics Desktop (EDT) HFFS such that the final designs will be able to achieve an operating frequency of 2.4GHz with a minimum return loss of -10dB for both singled-ended and differential-ended operations. The fine-tuning of the initial design has been done through changing of the initial design parameters.